Treatment of enuresis: a study with imipramine, amitriptyline, chlordiazepoxide-clidinium and piracetam - Yurdakök, Murat; Kınık, Erol; Bedük, Yaşar; Güvenç, Hüseyin; Us, Önder (The Turkish Journal of Pediatrics, 1986)
The effectiveness of the drugs used in the treatment of enuresis on 41 children are evaluated. Imipramine, amitriptyline, chlordiazepoxide-clidinium and piracetam were used at random on four different groups. Agreed the groups in all instances were small, but it was shown that 25-50 mg of imipramine administered at bedtime, produced a statistically significant improvement in children with nocturnal enuresis, when compared with the other drugs. Indeed piracetam was found to have no beneficial effect at all.